2007
DOI: 10.1016/j.lungcan.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Distress screening in a multidisciplinary lung cancer clinic: Prevalence and predictors of clinically significant distress

Abstract: SummaryScreening for distress in cancer patients is recommended by the National Comprehensive Cancer Network, and a Distress Thermometer has previously been developed and empirically-validated for this purpose. The present study sought to determine the rates and predictors of distress in a sample of patients being seen in a multidisciplinary lung cancer clinic. Consecutive patients (N = 333) were recruited from an outpatient multidisciplinary lung cancer clinic to complete the Distress Thermometer, an associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
240
9
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(307 citation statements)
references
References 52 publications
40
240
9
18
Order By: Relevance
“…Klank-RieXen et al (2007) found that 40.9% of 115 women with breast cancer expressed an interest in psychosocial support [6]. Graves et al [7] found that among 333 lung cancer patients, only 22.5% wanted help with their problems and, even in those with a high rate of distress, only 30% wanted help. In a crosssectional study of cancer patients in the Netherlands, Tuinman et al [8] screened 277 patients using the Distress Thermometer (DT) and the Hospital Anxiety and Depression Scale (HADS).…”
Section: Introductionmentioning
confidence: 99%
“…Klank-RieXen et al (2007) found that 40.9% of 115 women with breast cancer expressed an interest in psychosocial support [6]. Graves et al [7] found that among 333 lung cancer patients, only 22.5% wanted help with their problems and, even in those with a high rate of distress, only 30% wanted help. In a crosssectional study of cancer patients in the Netherlands, Tuinman et al [8] screened 277 patients using the Distress Thermometer (DT) and the Hospital Anxiety and Depression Scale (HADS).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the study questionnaire, levels of distress at the start and conclusion of the lung cancer screening visit were obtained using the NCCN Distress Thermometer (DT), a validated visual analog tool based on an ordinal rating scale from 0 (no distress) to 10 (extreme distress). [15] The DT instrument also includes a section designed to capture those factors influencing the distress score. The categories are subdivided as follows: practical problems (child care, housing, insurance/financial, etc.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Besides the well-described five stages of grief (denial, anger, bargaining, depression and acceptance) of KÜBLER-ROSS [58], which are commonly perceived in cancer patients from the very beginning of the disease, the following psychological symptoms and psychiatric disorders were attributed to patients in lung cancer-focused studies or systematic reviews [10,14,[59][60][61][62][63][64][65][66]: depression, anxiety, adjustment disorder, loss of libido, insomnia, suicidal thoughts, delirium, and nicotine and alcohol dependence. Psychological distress was described for all phases along the lung cancer trajectory, even in the favourable cases of survivors [67], but mental health was reported to deteriorate with progression of disease or impairment [68,69].…”
Section: Psychological Dimensionmentioning
confidence: 99%
“…Whilst increasing evidence has been published demonstrating successful implementation of palliative care or its elements into standard lung cancer care on the local level [23,62,[176][177][178], a superordinate master plan for better and encompassing delivery of palliative care in lung cancer patients is missing. For that, joint actions by governments and scientific societies are needed.…”
Section: Structure Processes and Time Of Integrationmentioning
confidence: 99%